Ethical axiological markers of Judaism: potencies of its humanistic effectiveness - Brodetskyi Oleksandr Yevhenovych (Studia Humanitatis, 2016)
The article concerns the moral resource of Judaic worldview ideas. The author analyzes anthropological grounds of Judaic ethics. The article considered the correlation between historically inherited conservative authoritarian elements and humanistic impulses in Judaic ethical values. The opportunities of tolerant cultivating of Judaic model of morality are revealed. The study is realized according to methodological approach of synergy of humanistic potencies of different religious ethical traditions and topicality of its social and personal developing effectiveness.